KEANEKARAGAMAN TUMBUHAN PENYUSUN VEGETASI HUTAN LINDUNG BENGKUNAT DI RESOR III KPH UNIT I PESISIR BARAT - Sesilia Maharani Putri; Indriyanto - (Lambung Mangkurat University-Indonesia, 2021)
Plant diversity in Protection Forest is an important factor that considered to support the sustainability function to protected the area. Plant diversity is a form of the species association that could be the indicator forest vegetation stabillities. This research aims to analyze the plant diversity in Bengkunat Protection Forest. This research was conducted between March-April 2019 at the 4,470 ha area with the sampling intensity 0.02%. Data were collected using grid line method that consisted of 34 sample plots. Data were analyz using Shannon Index (H), Richness Index (R) and Evenness Index (E). This study found 92 species at the research area. Dipterocarpus haseltii was the most dominant species based on Important Value Index (IVI) of 34.1%. While the average for other types of IVI is only 2.9%. The other dominated species were Polyalthia lateriflora, Dacryodes rostata and Dillenia excelsa. The forest species diversity index (H) was classified as moderate at 1.7, the Richness index (R) was classified as a high level of 30.4 and the evenness index (E) was classified as a high level of 0.9. Based on this research, Bengkunat Protection Forest diversity has a moderated value with the high diversity potential richness and evenness.